PENDIDIKAN INDONESIA: Dari Hegemoni dan Kuasa Pengetahuan ke Pendangkalan Kemanusiaan - Iskandar Zulkarnain (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2013)
This article discusses about hegemony and knowledge power (the authorities) which created less humanization in Indonesian education. This study uses IPS (social studies subject matter) as the object of the study. The result of the study shows three causes of less humanization in social sciences (IPS), namely: the first, the historical background of Indonesia is full of political and in doctrinal nuance. So the orientation of Indonesian education is automatically reduced for the authority’s interests. Second, the implementation of IPS teaching learning model is not flexible. It is monotones and homogeny. It is creates less critical thinking among students. The thirst, there was a symbolical violence in our education because of authorities superiority (teachers, schools) on students.